In Vitro Antimicrobial, Antioxidant and Cytotoxic activities of Polygonum orientale (Bishkatali) - Md. Tanjir Islam; Afrin Khan Priyanka; Tania Sultana; Md. Hassan Kawsar; Md. Helal Uddin Sumon; Md. Didaruzzaman Sohel (Journal of Pharmacy and Nutrition Sciences, 2016)
The aim of this present work is to investigate the antimicrobial, antioxidant and cytotoxic activities of methanol extract of Polygonum orientale (Family: Polygonaceae). Antimicrobial activity of methanol extract of Polygonum orientale was tested by Disc Diffusion Method. Standard antibiotic discs of Kanamycin (30µg/disc) for bacterial species was used as standard and crude extracts were used at a concentration of (20mg/disc) and (40mg/disc) for leaves and (10mg/disc) and (20mg/disc) for shoot extracts. The methanol extracts of leaves and shoots showed mild activity against gram positive bacteria, gram negative bacteria and fungi. Most of the organisms were susceptible to the extract in various degrees. The extract showed highest zone of inhibition (13mm) against the Gram (+)ve Bacillus megateriumand and gram (-)ve Escherichia coli (zone of inhibition 10mm). Antioxidant property of the plant extracts against stable DPPH (1, 1-Dipheny1-2-picrydrazole) radical was investigated. Ascorbic acid was used as standard. The extract was found low in antioxidant property. The absorbance was taken at 517nm by UV Spectrophotometer. The IC50 values were found in leaf extract and shoot extract are (1244.58µg/ml and (1506µg/ml). For ascorbic acid IC50 value was (139.19µg/ml). Cytotoxic activity of the crude extract by using Brine Shrimp Lethality Bioassay. Vincristin sulphate was used as standard. LC50 value of leaf extract was found (6.85µg/ml) and (9.7104µg/ml) for the shoot extract. In conclusion, the extract of the experimental plants have mild antimicrobial, low antioxidant and good cytotoxic properties.